Realizing Food Security from the Role of Women in the Family in Kolam Village Deli Serdang Regency - Ririn, Hasrinah; Harahap, Rahma Hayati (Journal of Peasants' Rights, 2024)
Food security can be defined as the availability of food in sufficient quantity and quality, distributed at affordable prices and safe for consumption for people to be able to carry out daily activities all the time. Food security cannot be separated from the role of women. Women are involved in production activities (on farm), processing and distribution of food. Women not only produce food, but are also the main person responsible for the nutritional needs of all family members. By nature, women, whether they act as housewives or heads of families, are the first to have a strategic role in selecting food ingredients, managing them, even processing and serving them to their household members. Women not only process food, but also must participate in the agricultural production process to ensure economic access to food. The gender gap in women's roles in agriculture disadvantages them in several ways.